Evolution of antimicrobial resistance of Gram-negative bacilli isolated from urinary-tract infections - Epidemiological study in a central hospital from 2010 to 2020 - Vinagreiro, Gabriela dos Santos (2022)
Trabalho Final do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina